(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Struggle over land and scarce resources have resulted in perennial and growing violent conflicts amongst arable crop farmers and cattle herdsmen in various parts of Nigeria. This study analyses the relationship between climate change and patterns of herders-crop farmers’ conflict in Zamfara state, Nigeria. Data for this study were acquired via semi structured questionnaire and Key Informant Interview. Purposeful sampling method was used to select six communities, while 260 farmers and 67 pastoralists were chosen as sample size for the survey based on Krejcie and Morgan’s formula. Descriptive statistics such as percentages, arithmetic mean and Likert rating scale were adopted to analyze the data for the study. Results from the findings indicated that farmers and herders in Zamfara state were within active years of economic and productive age (24 to 44 years). Nearly,75% of both farmers and pastoralists in the study communities professed there is high variability in rainfall pattern and increase in temperature. Three-quarter of the respondents confirmed that the nature of the conflicts was assault involving the use of arms; whereas two-fifth of the respondents affirmed that the conflict occurs during harvest and the planting seasons. The study concluded that climate change is the bane of incessant resource use conflicts in the study area. Thus a clearly formulated government policies and implementation framework that would boost climate change information forecasting and dissemination, adaptive capacity and ranch management will salvage the conflictual relationship subsisting between farmers and herders in the study area